Влияние экстернальных и интернальных факторов на трансформационные процессы в науке - Владленова, Илиана Викторовна (Гілея, 2014)
Целью данной статьи является исследование различных факторов, которые влияют на динамику и развитие современной науки. Выделены различные модели, описывающие динамику и развитие науки. В рамках различных моделей можно выделить исследования, в которых выделяются интернальные и экстернальные факторы, что определяет проблемный круг вопросов, которые оформляются в философском дискурсе. При акценте на экстернальных факторах исследования концентрируются в русле историзма, который признает важную роль социокультурного, исторического контекста в развитии научного знания, социологии знания и социальной эпистемологии, призванных выявлять социальные условия научной деятельности, рассматривать науку как социальный институт. Акцент на интернальных факторах смещает исследования в русло позитивистской традиции, логики, методологии науки, научного и структурного реализма. Выведено, что интернальные и экстернальные факторы действуют подобно двум фильтрам между компонентами науки, обусловливая стратегию научного поиска, поэтому их нельзя нивелировать.

The purpose of the article is to investigate various factors influencing modern science dynamics and development. The paper singles out different models describing the dynamics and development of science. Within the framework of such models there are works distinguishing internal and external factors, which defines the scope of research taking shape in the philosophical discourse. With the emphasis placed on the external factors, the scientists are swimming with the tide of historicism that gives special weight to the sociocultural, historical context in development of scientific knowledge (T. Kuhn), knowledge sociology and social epistemology called to expose the social conditions of scientific activities and to view science as a social institution. Among the theorists advocating the sociocultural aspect of studies of science, B. Barnes, G. Bachelard, P. Berger, D. Blur, G. Collins, Th. Luckman, K. Mannheim, R. Merton, S. Fuller deserve a mention for accentuating the external factors as the major driving forces in the development of scientific knowledge. The accent on the internal factors tilts the research towards positivistic traditions, logic, methodology of science, scientific and structural realism. N. Hanson, C. Hempel, W. V. Quine, K. Popper, S. Toulmin, K. Hübner and others were among the main contributors to the development of positivistic ideas.
Influence of external and internal factors on transformation processes in science
Keywords: историзм; логика; методология; критический реализм; science; external factors historicism; internal factors historicism; logic; methodology